The Influence of Self-Efficacy And Motivation on Interest in Reporting National Quality Indicators Through Healthcare Facility Registration Interest - Zahro, Siti Lailatus; Indasah, Indasah; Wardani, Ratna (Indonesian Journal of Global Health Research, 2025)
The lack of interest of independent medical practice healthcare facilities and independent dentist practice healthcare facilities in registering health facilities and reporting national quality indicators (national quality indicators) as a condition for accreditation will affect the quality of health facilities so that self-efficacy and motivation are really needed to increase this interest. The aim of this research is to analyze the influence of self efficacy and motivation on national quality indicators reporting interest through health facility registration interest as an intervening variable (study on independent medical practice healthcare facilities and independent dentist practice healthcare facilities in the kediri regency area). The research design used was analytical observational with a "cross sectional" approach. The sampling technique used was proportionate random sampling with a sample of 158 health facilities. Data were collected from 158 healthcare facilities in Kediri Regency using a structured questionnaire with a Likert scale (1–5). The questionnaire was distributed via WhatsApp and Google Forms, ensuring efficient and accessible data collection. The data analysis technique uses test path analysis. The research results show that in hypotheses 1,2,3,4,5 the significance value is <0.05 so that there is an influence of self-efficacy and motivation on interest in registering health service facilities, there is an influence of self-efficacy and motivation on interest in reporting national quality indicators , there is an influence of interest in registering health service facilities on interest in reporting national quality indicators , whereas in hypotheses 6 and 7 the significance result is >0.05 so it cannot prove that there is an influence of self-efficacy and motivation on interest in reporting national quality indicators through interest in registering service facilities. Health. The importance of awareness of health facilities, especially for independent medical practice healthcare facilities and independent dentist practice healthcare facilities, to carry out a series of accreditation steps to improve the quality of health facilities needs to receive more attention from the health service and independent medical practice healthcare facilities and independent dentist practice healthcare facilities as health service providers.